Decentralized Governance of Digital Platforms - Chen, Yan; Richter, Jack I.; Patel, Pankaj C. (Journal of Management, 2021)
Over the past decade, the rise of blockchain technology has led to the emergence of a growing number of decentralized platforms that are governed less by platform owners and more through community efforts. The emergence of blockchain platforms offers a unique opportunity to examine alternative structures for platform governance and to develop a theory around the value of centralized, semi-decentralized, and decentralized governance. Drawing on mechanism design theory, we evaluate the tradeoffs between centralization and decentralization and hypothesize semi-decentralization as a higher performing governance structure. Empirical evidence from the blockchain industry shows that decentralization has an inverted U-shaped relationship with platforms’ market capitalization, developer attention, and development activity. We further examine factors driving the decentralization of platform governance and find that digital platforms of the infrastructure layer—relative to those of the application layer—have a tendency to become more decentralized. This tendency, nevertheless, can be offset by experienced leaders to achieve semi-decentralization. Overall, this study contributes new insights on the characteristics, antecedents, and consequences of effective platform governance.